THE COMPARISON BETWEEN OUTDOOR LEARNING METHOD AND INDOOR LEARNING METHOD WITH STUDENT LEARNING PERFORMANCE SEEN FROM THE POINT OF VIEW OF STUDENT LEARNING ACTIVITY CLASS X OF TGB SMK NEGERI 2 SUKOHARJO IN KONSTRUKSI BANGUNAN ACADEMIC YEAR 2014-2015. - Valdera Yudistira; A G Thamrin; Waluyo Waluyo (Universitas Sebelas Maret, 2015)
The purpose of this study is: 1) To find out the influence of outdoor learning method and indoor learning method towards aniani4d student learning achievement. 2) To find out the difference of influence of learning activity from student learning achievement. 3) To find out interaction between outdoor learning method and indoor learning method towards student learning achievement. This study is an comparative. The technique of data collection uses documentation, method test, and questionnaire to search data about achievement and student learning activity. The validity of the research instruments uses validity, reliability, and power of different difficulty levels. Test requirements analysis consists of the normality test and homogeneity test. The technique of data analysis uses a hypothesis test with ANAVA two studies. Based on the results of this study concluded: 1) There was influence between outdoor learning method and indoor learning method toward student learning achievement. 2) There was no difference of influence of learning activity towards student learning achievement. 3) There was no interaction between outdoor learning method and indoor learning method towards student learning achievement. Key word: Learning Method, Outdoor Learning, Indoor Learning, Learning Activity, Learning Achievement